2021
DOI: 10.1155/2021/5932222
|View full text |Cite
|
Sign up to set email alerts
|

Effective and Simple NaOH-Modification Method to Remove Methyl Violet Dye via Ipomoea aquatica Roots

Abstract: In this study, a simple chemical modification was applied to a sustainable and abundantly available resource, kangkong root (KR), to remove methyl violet 2B (MV) dye. The chemically modified adsorbent (NaOH-KR) was obtained using NaOH solution treatment. Batch adsorption experiments were carried out to investigate the effects of pH, ionic strength, contact time, adsorbent dosage, and initial dye concentration. A regeneration experiment was also carried out to assess the potential of reusability. The adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The highest adsorption capacity was 551.5 mg/g in NaOH-treated Ipomoea aquatica root based on the Sips model [145]. SEM images demonstrated that different morphologies could be observed in the untreated (flat surface) and NaOH-treated Ipomoea aquatica root (irregular and rough surface).…”
Section: Ipomoea Aquatica Rootmentioning
confidence: 96%
“…The highest adsorption capacity was 551.5 mg/g in NaOH-treated Ipomoea aquatica root based on the Sips model [145]. SEM images demonstrated that different morphologies could be observed in the untreated (flat surface) and NaOH-treated Ipomoea aquatica root (irregular and rough surface).…”
Section: Ipomoea Aquatica Rootmentioning
confidence: 96%
“…The abundantly available kangkong root can be used to remove dyes; Lu et al [ 20 ] used it to remove methyl violet. They were primarily concerned with the recovery and reuse of the dye and concluded that sodium-hydroxide-modified kangkong root could sustain dye removal after five consecutive cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin is a broad term for a large group of aromatic polymers formed by the combinatorial oxidative coupling of 4-hydroxy phenylpropanoids ( Figure 1 ). The elemental composition and methoxyl content of lignin in spruce wood is 63.84% carbon, 6.04% hydrogen, 29.68% oxygen, and 15.75% methoxyl [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural adsorbents, including wheat straws, rye straws, rice straws, peanut husks, corn cobs, Jerusalem artichoke stems, biochar, and biomass, offer advantages for the removal of dyes from wastewater, due to their abundant availability [ 7 ]. These biopolymers possess inherent properties that make them effective adsorbents.…”
Section: Introductionmentioning
confidence: 99%